How do arbuscular mycorrhizas affect reproductive functional fitness of host plants? - Wang, Lei; Tang, Zhanhui (Frontiers in Plant Science, 2022)
Arbuscular mycorrhizal symbiosis in soil may be directly or indirectly involved in the reproductive process of sexually reproducing plants (seed plants), and affect their reproductive fitness. However, it is not clear how underground arbuscular mycorrhizal symbiosis affects plant reproductive function. Here, we reviewed the studies on the effects of mycorrhizal symbiosis on plant reproductive fitness including both male function (pollen) and female function (seed). Mycorrhizal symbiosis regulates the development and function of plant sexual organs by affecting the nutrient using strategy and participating in the formation of hormone networks and secondary compounds in host plants. The nutrient supply (especially phosphorus supply) of mycorrhizal may be the main factor affecting plant’s reproductive function. Moreover, the changes in hormone levels and secondary metabolite content induced by mycorrhizal can also affect host plants reproductive fitness. These effects can occur in pollen formation and transport, pollen tube growth and seed production, and seedling performance. Finally, we discuss other possible effects of mycorrhizal on the male and female functional fitness, and suggest several additional factors that may be involved in the influence of mycorrhizal on the reproductive fitness of host plants. We believe that it is necessary to accurately identify and verify the mechanisms driving the changes of reproductive fitness of host plant in symbiotic networks in the future. A more thorough understanding of the mechanism of mycorrhizal symbiosis on reproductive function will help to improve our understanding of mycorrhizal ecological roles and may provide references for improving the productivity of natural and agricultural ecosystems.